Kebutuhan Dan Ketersediaan Modal Kerja Dalam Hubungannya Dengan Profitabilitas Perusahaan (Studi pada PT. Persada Lampung Raya) - Habiburrahman HABIBURRAHMAN; Daniel Hariadi Sunjoto; Riswan RISWAN (Universitas Bandar Lampung (UBL), 2011)
The purpose of this study was to determine how the use of working capital to the company's profitability to fluctuate as well as to determine the exact amount of working capital as needed PT. Lampung Persada Raya. The hypothesis is that